2012
DOI: 10.1002/acp.2897
|View full text |Cite
|
Sign up to set email alerts
|

Going Gaga: Investigating, Creating, and Manipulating the Song Stuck in My Head

Abstract: Summary: Having a song stuck in your head is a commonly experienced intrusive thought. We explored the intrusive song phenomenon through a survey, an experimental diary study, and three laboratory experiments. Contrary to the belief that only obnoxious songs get stuck, we found that songs people know and like frequently became intrusive. We also found that intrusive songs followed environmental cues. In addition, if a song continued to play in someone's head immediately after listening to it, the song was like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
168
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(207 citation statements)
references
References 45 publications
28
168
3
Order By: Relevance
“…The effects of positive mood replicate and extend recent research on pleasantness of musical imagery (e.g., Beaman andWilliams, 2010 andHyman et al, 2013). At first glance, the effects of negative mood might imply that musical imagery was anxietyprovoking to some people.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The effects of positive mood replicate and extend recent research on pleasantness of musical imagery (e.g., Beaman andWilliams, 2010 andHyman et al, 2013). At first glance, the effects of negative mood might imply that musical imagery was anxietyprovoking to some people.…”
Section: Discussionsupporting
confidence: 80%
“…Such imagery has been linked to positive affective states prior to onset (Williamson et al, 2011) and during the experience . Recently, Hyman et al (2013) found that imagery was more commonly reported for songs that were liked rather than disliked. This finding is complimented by research suggesting musical imagery is rarely experienced as aversive or disruptive in daily life.…”
Section: Musical Imagery and Volitional Controlmentioning
confidence: 99%
“…The majority of GTP-ATB experiences occurred in a social context and the activities reported by gamers included being engaged in automated behaviours such as walking, driving, and packing. This finding appears to mirror research into mind wandering (Smallwood & Schooler, 2006), musical imagery (Hyman et al, 2012), and GTP identified in other modalities (Ortiz de Gortari & Griffiths, 2013). GTP-ATB also occurred when gamers felt tired, sleep deprived, and stressed.…”
Section: Discussionsupporting
confidence: 67%
“…In fact, music is one of the most effective ways to induce mood in experimental psychology studies (Kenealy, 1988). A considerable amount of literature has been published on the effects of music (Blood & Zatorre, 2001), as well as the phenomenology of re-experiencing auditory cues in an absence of auditory stimuli in clinical and non-clinical populations (Hyman et al, 2012;Liikkanen, 2012). However, only a few studies have focused on exploring the effects of videogames' auditory cues on gamers during playing (Hebert, Beland, Dionne-Fournelle, Crete, & Lupien, 2005).…”
mentioning
confidence: 99%